Сучасні трансформаційні процеси на ринку праці України - Скопенко, Наталія Степанівна; Євсєєва-Северина, Ірина Василівна (My University, 2023)
В статті розглянуто зміни, що відбулися на українському ринку праці в період війни. Акцентовано увагу, що вітчизняний мікро- та малий бізнес постраждав від воєнної кризи найбільше, багато компаній припинили своє існування. Компанії, що впоралися з викликами зовнішнього середовища, основними пріоритетами діяльності виділяють збереження бізнесу, клієнтів та команди, а також допомогу українським захисникам. Вітчизняний бізнес приділяє значну увагу благополуччю співробітників, пропонуючи релокейт сімей закордон або внутрішню міграцію в безпечніші регіони України, впроваджуючи програми психологічної допомоги своїм працівникам. В той же час, український ринок праці зазнав суттєвих змін: підвищується попит на вакансії таких спеціалістів як: будівельники, монтажники, вантажники, комплектувальники, пакувальники товарів, продавці, спеціалісти ІТ, фармацевти тощо. Враховуючи нові реалії сьогодення, роботодавці змушені переглядати свою кадрову політику, що проявляється у зменшенні бонусів та премій, скороченні персоналу, зменшенні зарплат, стимулюванні працівників до самонавчання та вдосконалення професійних навичок. Відповідно до стрімких процесів діджиталізації, 40—50% нинішніх співробітників компаній потребуватимуть професійної перепідготовки. Політика держави та розробка програм щодо фінансування перепідготовки чи підвищення кваліфікації робітників за публічні кошти повинна допомогти вирішити питання забезпечення потреби у кваліфікованих працівниках для повоєнної відбудови України. The article examines the changes that occurred in the Ukrainian labor market during the war. It is emphasized that domestic micro and small businesses have suffered the most from the military crisis, and many companies have ceased to exist. The partial and complete loss of production facilities due to constant shelling and alienation of territories led to the loss of market positions, the need to implement rapid changes, relocate businesses, and radically restructure operations. At the same time, migration caused by the war has led to a shortage of specialists and disrupted the balance of labor between regions. Companies that have coped with the challenges of the external environment prioritize maintaining their business, customers, and team, as well as helping Ukrainian defenders. Ukrainian companies pay attention to the well-being of employees, offering family relocation abroad or internal migration to safer regions of Ukraine, and implementing psychological assistance programs for their employees. Recent experience has shown that attention to employee well-being helps to achieve high productivity of the team. The higher the level of employee satisfaction, the better they work, that is why well-being programs are becoming part of the corporate culture of modern companies. At the same time, the Ukrainian labor market has undergone significant changes: there is a growing demand for vacancies for such specialists as builders, installers, loaders, pickers, packers, salespeople, IT specialists, pharmacists, etc. According to the challenge of new realities, employers are forced to revise their HR policies, which manifests itself in the reduction of bonuses, staff reductions, salary cuts, and encouragement of employees to self-study and improve their professional skills. Changes that are occurring at a rapid pace in all areas require modern employees to be flexible and capable of continuous learning and retraining. Due to the rapid digitalization processes, 40—50% of current employees will need professional retraining. Government policy and the development of programs to finance retraining or professional development of workers at public expense should help to address the need for skilled workers for the post-war reconstruction of Ukraine.
Keywords: ринок праці; кадри; війна; програми well-being; перекваліфікація; labor market; personnel; war; well-being programs; retraining; кафедра економіки праці та менеджменту